2017
DOI: 10.1097/md.0000000000006534
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes in normal appearing white matter in multiple sclerosis patients using multivoxel magnetic resonance spectroscopy imaging

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Almost half of the surveyed papers employed magnetic resonance spectroscopic imaging (MRSI) instead of single-voxel acquisition schemes, including echo-planar spectroscopic imaging (EPSI) (85, 89, 124, 144, 145, 221–223), and other CSI or spectroscopic imaging sequences encoded in two (25, 28, 30, 34, 36, 41, 43, 45, 50, 52, 54, 57, 6062, 6466, 68, 72, 73, 80, 81, 83, 87, 93, 94, 115, 119, 130, 131, 133, 135, 141, 159, 162165, 167, 168, 174, 188, 191, 194, 204, 224231) or three (102, 121, 122, 137, 202, 232, 233) spatial dimensions. MRSI offers the obvious advantage of enabling metabolic profiling over a large area of multiple tissue types, thereby enabling averaging over gray matter, white matter, and lesions within the same individual, enabling more robust estimates for the metabolic patterns of hypothetically pure tissue (102, 104, 163, 164).…”
Section: Spectral Acquisition and Processingmentioning
confidence: 99%
“…Almost half of the surveyed papers employed magnetic resonance spectroscopic imaging (MRSI) instead of single-voxel acquisition schemes, including echo-planar spectroscopic imaging (EPSI) (85, 89, 124, 144, 145, 221–223), and other CSI or spectroscopic imaging sequences encoded in two (25, 28, 30, 34, 36, 41, 43, 45, 50, 52, 54, 57, 6062, 6466, 68, 72, 73, 80, 81, 83, 87, 93, 94, 115, 119, 130, 131, 133, 135, 141, 159, 162165, 167, 168, 174, 188, 191, 194, 204, 224231) or three (102, 121, 122, 137, 202, 232, 233) spatial dimensions. MRSI offers the obvious advantage of enabling metabolic profiling over a large area of multiple tissue types, thereby enabling averaging over gray matter, white matter, and lesions within the same individual, enabling more robust estimates for the metabolic patterns of hypothetically pure tissue (102, 104, 163, 164).…”
Section: Spectral Acquisition and Processingmentioning
confidence: 99%
“…Marked damage to the frontal regions was also noticed in the study on patients with MS [44]. A different pattern of damage to NAWM was observed in a study of Asian patients with MS, which revealed that the largest decrease in NAA was in parietal NAWM [45].…”
Section: Discussionmentioning
confidence: 72%
“…For example, brain metabolism plays a major role in pathogenesis of some neurological disorders such as Alzheimer’s disease 17 - 19 by hypometabolismpromoted Aβ deposition. 20 Furthermore, the findings based on proton magnetic resonance spectroscopy have shown the alteration of metabolite concentration in various areas of the brain in different neurometabolic disorders such as multiple sclerosis, 21 brain tumors, 22 , 23 epilepsy, 24 , 25 Alzheimer disease, 26 - 28 and dementia 29 is significantly correlated with cognitive decline. Based on the abovementioned studies, metabolic diseases of the brain can lead to changes in the structure and function of brain areas associated with cognition; most metabolic diseases of the brain cause changes in neuronal structure and cognitive decline.…”
Section: Cognitive Changes In Metabolic Syndromementioning
confidence: 99%